The influence of talent management on employee performance mediated by organizational culture - Anang Septiyadi; Muhamad Ekhsan (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of Talent Management on Employee Performance mediated by Organizational Culture at PT Astra Honda Motor Cikarang. Research object at PT Astra Honda Motor Cikarang. This research was conducted using quantitative methods with SEM Smart PLS software as the analysis. The number of samples obtained by random sampling technique using the slovin formula amounted to 77 respondents. Data collection is done using google form in filling out online surveys. The data analysis method used is the R-square test, Bootstrapping, Path Coefficient, and Specific indirect effects. The results of this study indicate that Organizational Culture has a positive and significant effect on Employee Performance, Talent Management has a positive and significant effect on Organizational Culture, Talent Management has a positive and significant effect on Employee Performance, Organizational Culture has a positive and significant effect in mediating Talent Management on Employee Performance. This research aims to uncover the influence of talent management on employee performance while examining the mediating role of organizational culture. By unraveling the underlying mechanisms, this study will contribute to both academia and practice, providing valuable insights to organizations seeking to enhance their talent management practices and foster a high-performance culture.